First and Second Generation Impacts of the Biafran War - Richard Akresh; Sonia R. Bhalotra; Marinella Leone; Una O. Osili (Institute of Labor Economics (IZA), 2017)
We analyze long-term impacts of the 1967-1970 Nigerian Civil War, providing the first evidence of intergenerational impacts. Women exposed to the war in their growing years exhibit reduced adult stature, increased likelihood of being overweight, earlier age at first birth, and lower educational attainment. Exposure to a primary education program mitigates impacts of war exposure on education. War exposed men marry later and have fewer children. War exposure of mothers (but not fathers) has adverse impacts on child growth, survival, and education. Impacts vary with age of exposure. For mother and child health, the largest impacts stem from adolescent exposure.
Keywords: I12; I25; J13; O12; 330; intergenerational; conflict; human capital; fetal origins; Africa